Protagonismo politico e social na velhice: cenários, potencias e problemáticas - Rozendo, Adriano da Silva [UNESP]; Justo, José Sterza [UNESP]; Correa, Mariele Rodrigues [UNESP] (My University, 2010)
The active presence of the old ones in the society brings up discussions about the political and social participation in the advanced ages of the life. The senior citizen, like an actor of great relevance in the present time, shows their potential as scriptwriter and protagonist of their own history. However, many spaces constituted vertically, turned for this aim become artificial, abolishing, many times, the spontaneity and potential of these actors. Anyway, the important thing is to open spaces for the different expressions of social participation and that they find their legitimacy and place in the set of the protagonism that attaches life and sense to the world.

A presença cada vez mais ativa dos idosos na sociedade traz à tona discussões sobre a participação política e social nas idades avançadas da vida. O idoso, como um ator de grande relevância na atualidade, vem mostrando seu potencial como roteirista e protagonista da sua própria história. Contudo, muitos espaços constituídos verticalmente, voltados para este fim, tornam-se artificiais e acabam suprimindo a espontaneidade de muitas protagonizações. Seja como for, o importante é abrir espaços para as diferentes expressões de participação social e que elas encontrem sua legitimidade e lugar no conjunto dos protagonismos que dão vida e sentido ao mundo.
Political and social protagonism in the old age: sceneries, potentialities and problems
Keywords: Senior citizen; Protagonism; Society; Idoso; Protagonismo; Sociedade